SEALING PERFORMANCE OF GASKETED FLANGE JOINTS – A PARAMETRIC STUDY - Abid, Muhammad; Chattha, Javed A; Khan, Kamran A; Wajid, Hafiz A (IIUM Engineering Journal, 2014)
ABSTRACT: This paper aims at finding the leak rate through ANSI class#150 flange joints using compressed asbestos sheet gasket under combined structural and thermal transient loading conditions. The solution is obtained using two different leak rate models and two different bolt up values. The gasket compressive strain based model employs strains that are determined using finite element analysis. The other model is based on the porous media theory in which gasket is considered as porous media. Leak rates determined using these leak rate models are compared for different tightness classes and discussed. ABSTRAK: Kajian bertujuan mencari kadar bocor menerusi sambungan bebibir kelas ANSI#150 menggunakan gasket kepingan asbestos termampat di bawah kondisi bebanan gabungan struktur dan terma fana. Solusinya diperolehi dengan menggunakan dua model kadar bocor yang berbeza dan dua nilai atas bolt yang berlainan. Model terikan berasaskan pemampat gasket menggunakan terikan yang ditentukan dengan analisis unsur terhingga. Model yang lainnya berasaskan teori bahantara berongga di mana gasket digunakan sebagai medium. Kadar bocor ditentukan dengan menggunakan model kadar bocor, yang kemudiannya dibandingkan pada kelas keketatan yang berbeza dan keputusannya dibincangkan. KEYWORDS: bolted flange; gasket; leak rate; finite element analysis; tightness class compressive strains; porous media <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>